EFFICIENCY OF NON-LIFE INSURANCE IN INDONESIA - Zaenal Abidin; Emilyn Cabanda (Universitas Hayam Wuruk Perbanas, 2011)
It is a fact that financial institutions among Asian countries, especially Indonesia, have beendominated by commercial banks. In addition, an insurance market share is only 10 percent ofthe financial market. Yet, the insurance industry is an important partner for the banking industry.This function is to guarantee the risk of banks in distributing credit and supportingthe national economy through the community's fund. This paper evaluates the relative efficiencyof 23 Non Life Insurance companies in Indonesia, using Data Envelopment Analysis(DEA) model. DEA is a management evaluation tool that assists in identifying the most efficientand inefficient decision-making units (DMUs) in the best practice frontier. Empiricalresults show that bigger insurance companies are found to be more efficient than smallerfirms. Moreover, companies with captive market and the company's group with non-captivemarket have relatively the same result. These findings are new empirical contributions toefficiency literature of the insurance industry. The paper also provides policy implicationsfor the Indonesian insurance sector.